A Comprehensive Lifestyle Randomized Clinical Trial: Design and Initial Patient Experience. (March 2017) - Arun, Banu; Austin, Taylor; Babiera, Gildy V.; Basen-Engquist, Karen; Carmack, Cindy L.; Chaoul, Alejandro; Cohen, Lorenzo; Connelly, Lisa; Haddad, Robin; Harrison, Carol; Li, Yisheng; Mallaiah, Smitha; et al.
Background: Although epidemiological research demonstrates that there is an association between lifestyle factors and risk of breast cancer recurrence, progression of disease, and mortality, no comprehensive lifestyle change clinical trials have been conducted to determine if changing multiple risk factors leads to changes in biobehavioral processes and clinical outcomes in women with breast cancer. This article describes the design, feasibility, adherence to the intervention and data collection, and patient experience of a comprehensive lifestyle change clinical trial (CompLife). Methods: CompLife is a randomized, controlled trial of a multiple-behavior intervention focusing on diet, exercise, and mind-body practice along with behavioral counseling to support change. The initial exposure to the intervention takes place during the 4 to 6 weeks of radiotherapy (XRT) for women with stage III breast cancer and then across the subsequent 12 months. The intervention group will have 42 hours of in-person lifestyle counseling during XRT (7-10 hours a week) followed by up to 30 hours of counseling via video connection for the subsequent 12 months (weekly sessions for 6 months and then monthly for 6 months). The primary outcome is disease-free survival. Multiple secondary outcomes are being evaluated, including: (1) biological pathways; (2) overall survival; (3) patient-reported outcomes; (4) dietary patterns/fitness levels, anthropometrics, and body composition; and (5) economic outcomes. Qualitative data of the patient experience in the trial is collected from exit interviews, concluding remarks, direct email correspondences, and web postings from patients. Results: Fifty-five patients have been recruited and randomized to the trial to date. Accrual of eligible patients is high (72%) and dropout rates extremely low (5%). Attendance to the in-person sessions is high (95% attending greater than 80% of sessions) as well as to the 30 hours of video counseling (88% attending more than 70% of sessions). Adherence to components of the behavior change intervention is high and compliance with the intensive amount of data collection is exceptional. Qualitative data collected from the participants reveals testimonials supporting the importance of the comprehensive nature of intervention, especially the mind-body/mindfulness component and social support, and meaningful lifestyle transformations. Conclusion: Conducting a comprehensive, multicomponent, lifestyle change clinical trial for women with breast was feasible and collection of biobehavioral outcomes successful. Adherence to behavior change was high and patient experience was overwhelmingly positive.